2013
DOI: 10.14366/usg.13003
|View full text |Cite
|
Sign up to set email alerts
|

Giant cavernous hemangioma coexistent with diffuse hepatic hemangiomatosis presenting as portal vein thrombosis and hepatic lobar atrophy

Abstract: A combination of giant hepatic hemangioma and diffuse hemangiomatosis is extremely rare in adults. Even when they are large, hemangiomas are soft and rarely compress adjacent structures. A 78-year-old man presented with abdominal pain and distension. Ultrasonography, computed tomography, and magnetic resonance imaging demonstrated a large expansile mass replacing the medial segment and caudate lobe with diffusely scattered nodules in the entire liver. The large hilar mass contained a central nonenhancing area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…3 Notably, DHH is associated with giant cavernous hemangioma (GCH), a cavernous hemangioma >5 cm in size, in more than half of the cases. 2,13,14 DHH usually affects infants and children. A female preponderance is noted among the adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Notably, DHH is associated with giant cavernous hemangioma (GCH), a cavernous hemangioma >5 cm in size, in more than half of the cases. 2,13,14 DHH usually affects infants and children. A female preponderance is noted among the adults.…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search till May, 2022 along with the literature review by He et al 6 showed only 19 reported cases of adult DHH depicted in the English literature. 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Approximately half of the DHH cases can be seen in association with GCH. 2 The etiopathogenesis of DHH is uncertain, although it has been diagnosed in association with hereditary disorders, such as skeletal hemangiomatosis and Osler-Weber-Rendu disease, and drugs like oral contraceptives (OC) and metoclopramide.…”
Section: Introductionmentioning
confidence: 99%
“…Additional reports of hemangiomatosis associated with a giant hemangioma have been described after that one [4 , [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse haemangiomas in liver (haemangiomatosis) might be associated with some syndromes such as Osler-Weber-Rendu disease [13] and medications such as estrogen [14] and metoclopramide [15] with a female predilection. These may present with abdominal pain, distension, weight loss, fever, night sweats, and jaundice.…”
Section: Adult Hepatic Haemangiomamentioning
confidence: 99%